2014
DOI: 10.4236/ojog.2014.42014
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease as potential obstacle to childbearing

Abstract: AIM: The authors have aimed at confirming or excluding gluten sensitivity in infertile couples. PATIENTS AND METHODS: Between 2004 and 2010, at our outpatient clinics of immunology, both partners of 223 couples, who had striven for having a child unsuccessfully, underwent history taking, physical examination, laboratory and immuno-serologic tests including anti-tissue-transglutaminase antibody (anti-tTG), as well as deep duodenal biopsy in antibody-carrying patients. RESULTS: Antibodies against tissue transglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The consequence of the current study revealed that, this autoantibody have no effects on normozoospermia and oligozoospermia ,although the previous study mentioned that 90% of deficiency of spermatozoa in the semenis idiopathic ,but our finding not confirm any respect between IgA anti tTG and this parameter, sothat oligozoospermia may be belong to other reasons such as environmental, geneticor certain medications (16) .Our results also detected that the percentage of incidence of Ig A -tTGA in the infertile men was equal to 4% that is meant the celiac disease was not implicated in the pathomechanism of infertility in the men. Furthermore this outcome was in accord with previous research which mentioned that, a two male out of 223 (or about 0.9% )tested positive for these autoantibodies (17) (Kovács et al,2014).As well as this finding is agreement with previous which denoted thatdoes not find any effect for celiac disease prevalence in infertile male (18) In addition to that, although, the findings of present study showed that there is a high significant difference in sperm concentration between IgA-tTG antibodies positive and negative male infertility patients, but this outcome not means that, these autoantibodies have critical role in the spermatogenesis, thus this results may be due to other factors such as, growth hormone which possess role in process of the production or development of mature spermatozoa, as mentioned to that Magon et al, (19). Or this result may be attributed to overweight or obesity, where 35.9% of patient were overweight, while 30.77% were obese,thereby this factor influences on the spermatogenesis as denoted to that Palmer et al, (20) in theirstudy.…”
Section: Discussionsupporting
confidence: 92%
“…The consequence of the current study revealed that, this autoantibody have no effects on normozoospermia and oligozoospermia ,although the previous study mentioned that 90% of deficiency of spermatozoa in the semenis idiopathic ,but our finding not confirm any respect between IgA anti tTG and this parameter, sothat oligozoospermia may be belong to other reasons such as environmental, geneticor certain medications (16) .Our results also detected that the percentage of incidence of Ig A -tTGA in the infertile men was equal to 4% that is meant the celiac disease was not implicated in the pathomechanism of infertility in the men. Furthermore this outcome was in accord with previous research which mentioned that, a two male out of 223 (or about 0.9% )tested positive for these autoantibodies (17) (Kovács et al,2014).As well as this finding is agreement with previous which denoted thatdoes not find any effect for celiac disease prevalence in infertile male (18) In addition to that, although, the findings of present study showed that there is a high significant difference in sperm concentration between IgA-tTG antibodies positive and negative male infertility patients, but this outcome not means that, these autoantibodies have critical role in the spermatogenesis, thus this results may be due to other factors such as, growth hormone which possess role in process of the production or development of mature spermatozoa, as mentioned to that Magon et al, (19). Or this result may be attributed to overweight or obesity, where 35.9% of patient were overweight, while 30.77% were obese,thereby this factor influences on the spermatogenesis as denoted to that Palmer et al, (20) in theirstudy.…”
Section: Discussionsupporting
confidence: 92%
“…Among women, anti-tTG positivity was detected in 11/500 (2.2 %), and the diagnosis of CD could be confirmed by histological examination in 8/500 (1.6 %) of them. As a result of a strict gluten-free A curiosity of our study: we could demonstrate previously unrecognized CD in both members of a couple, and then at a gluten-free diet they had, via spontaneous conception a healthy offspring in 2011 (95,96). At a gluten-free diet, no positivity was shown in the child by periodic anti-tTG tests.…”
Section: Celiac Disease In Relation To Reproductive Failuresmentioning
confidence: 61%
“…Hungarian and international literature (92,93,94,95,96), and successful conception of 155 children occurred during our treatments. As far as we know, we published on this topic as first in Hungary.…”
Section: Anti-sperm Antibody In Relation To Reproductive Failuresmentioning
confidence: 79%